2019
DOI: 10.7251/vetjen1901083p
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Thrombocytopenia in Dogs - Case Report

Abstract: Thrombocytopenia represents a significant reduction in number of blood platelets in thecirculation of mammals. The causes of thrombocytopenia in dogs and cats are: various infectiousfactors, viruses, bacterias, parasites, various pathological conditions of the liver, spleen, bonemarrow or autoimmune diseases. Sometimes, thrombocytopenia causes many different factors orthe real cause can not be detected, and its origin is called idiopathic. In our practice, in the course ofhaematological analysis of blood, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…200 They did however conclude that regulatory changes as a rule have to be "reasonable, proportionate and in line with public interest" to be acceptable, and found that they had been in case of Charanne. 201 One of the arbitrators dissented, and argued that the legal framework itself could give rise to legitimate expectations. 202 In Isolux, the tribunal reached a similar conclusion as in Charanne, but one of the arbitrators dissented along the same lines as his colleague previously.…”
Section: Legal Stability and Legitimate Expectationsmentioning
confidence: 99%
“…200 They did however conclude that regulatory changes as a rule have to be "reasonable, proportionate and in line with public interest" to be acceptable, and found that they had been in case of Charanne. 201 One of the arbitrators dissented, and argued that the legal framework itself could give rise to legitimate expectations. 202 In Isolux, the tribunal reached a similar conclusion as in Charanne, but one of the arbitrators dissented along the same lines as his colleague previously.…”
Section: Legal Stability and Legitimate Expectationsmentioning
confidence: 99%
“…The Tribunal concluded, correctly in our view, that SCI's cost advantage ought to be taken into account at some stage of the inquiry. 34 The Tribunal noted that SCI's approach instead leads to an artificial result, and that it was not practical that if in SCI's notional exercise prices were found not to be above economic value, special cost advantages could never be considered ever again in the analysis. The Tribunal's interpretation of the CAC's decision in Mittal was that a broader and more holistic view, including the realities of the market, must be taken when considering special cost advantages.…”
Section: Special or Not? What Makes Sense In The South African Context?mentioning
confidence: 99%
“…Neotel's subsequent complaint against Telkom 32 was referred by Icasa to the Complaints and Compliance Committee (CCC). 33 The CCC 34 is a mechanism for resolving disputes. Alternatively, Icasa could impose a remedy unilaterally or negotiate with the parties to resolve a matter.…”
Section: Regulation and Competition: Facilities Leasingmentioning
confidence: 99%
“…It looks like the kind of balancing performed in the South African private eviction case of City of Johannesburg Metropolitan Municipality v. Blue Moonlight Properties 39 (Pty) Ltd and Another.142 In this case the court found that a private landowner could be expected to have some delay in regaining possession of its property, especially since it bought the property for commercial purposes (not for housing) and knew full well that it was unlawfully occupied. 143 The fact that the property, in Brežec v. Croatia, was initially state-owned and used for social housing does not make it a state eviction. Instead, it justifies the outcome of the proportionality analysis since these factors weigh in the balance.…”
Section: The Court's Power and Duty To Allow The Proportionality Defencementioning
confidence: 99%